Pedagogical aspects of development of music minimalism - D.V. Androsova (Academy of Cognitive and Natural Sciences, 2006)
Pedagogical aspects of development of music minimalism. The paper is devoted to the characteristic of the didactical bases of music of minimalism - as creativity of the composers, and of performans style. An harmonical orientation of symbolics and extatic of minimalism acctened tn conditionality of his meaning by structure of archetypes.